Factors Affecting Employee Performance: Discipline, Motivation, and Environment at a Service Company in Jakarta - Vindiana, Afina Putri; Artono, Mukti (Institut Teknologi Indonesia, 2025)
Amid the intense business competition, the quality of human resources has become a crucial element in determining a company's success in achieving its goals. PT XYZ, which operates in the service sector, recognizes that employee performance plays a vital role in supporting productivity and the continuity of its operations. However, the company continues to face several challenges, such as low levels of discipline, fluctuating work motivation, and an unsupportive work environment, all of which have the potential to affect employee performance. The purpose of this study is to examine the extent to which work discipline, employee motivation, and work environment conditions influence employee performance at PT XYZ. This research employs a descriptive quantitative approach using simple linear regression analysis. Data were collected through questionnaires distributed to 90 employees selected using purposive sampling. The research instruments have been tested for validity and reliability, and were found to meet the required testing criteria. The results of the study show that discipline and environment have a positive and significant influence on employee performance. Discipline fosters a sense of responsibility, while a conducive work environment supports comfort and efficiency. These two variables play an important role in enhancing performance. Therefore, it is recommended that the management of PT XYZ continue to instill a culture of discipline and create a supportive work environment to improve productivity and job satisfaction.